Forecasting Water Use for Electric Power Generation. - Young, H; Thompson, R (American Geophysical Union, 1973)
Knowledge of demand functions for water and electricity provides a basis for forecasting water withdrawals, water consumption, and heat discharges to the water in electric power generation. The variables in these demand functions may be significantly affected by direct and indirect variations in policy. Forecasts of water withdrawals and consumption of water are made for alternative combinations of the variables in the demand functions and compared with the results of previous studies in which the demands for water were forecast as ‘requirements.’